TCSC: A Trustworthy and Communal Social Classifieds - Chuang, Yung-Ting (Discoveries in Agriculture and Food Sciences, 2017)
Today, everyone relies heavily on the Internet to access information, and it changes the way we live, including our use of social networking services and community-based classified systems. However, two major problems lurk behind both social networking and community-based classified systems. privacy and security. First, the current systems could be modified someday to filter, conceal or censor information. Second, the anonymity inherent in the community-based classifieds does not provide any safeguard to the users. In order to address the privacy concerns and give better protection to the users, we present a trustworthy and communal social classifieds, named TCSC, in this paper. Our TCSC is a decentralized communal social classifieds infrastructure, and it contains: 1) distributed search and retrieval system, 2) reputation system, 3) protection system, and 4) randomized message routing system. We further demonstrate that our TCSC can accurately and retain significant utility even in the presence of malicious nodes.